Antibiotic Susceptibility of Escherichia coli Among Infants Admitted to Neonatal Intensive Care Units Across the US From 2009 to 2017 - Flannery, Dustin D. (JAMA Pediatr, 2020)
IMPORTANCE: Escherichia coli is a leading cause of serious infection among term and preterm newborn infants. Surveillance of antibiotic susceptibility patterns of E coli among infants admitted to neonatal intensive care units should inform empirical antibiotic administration. OBJECTIVE: To assess the epidemiologic characteristics and antibiotic susceptibility patterns of E coli in infants admitted to neonatal intensive care units in the US over time. DESIGN, SETTING, AND PARTICIPANTS: This retrospective cohort study used the Premier Health Database, a comprehensive administrative database of inpatient encounters from academic and community hospitals across the US. Participants included newborn infants admitted to centers contributing microbiology data from January 1, 2009, to December 31, 2017, with E coli isolated from blood, cerebrospinal fluid, or urine cultures. Data were collected and analyzed from December 1, 2018, to November 30, 2019. MAIN OUTCOMES AND MEASURES: Changes in annual antibiotic susceptibility of E coli during the study period. The proportion of infants with nonsusceptible organisms (resistant or intermediate susceptibility) in antibiotic categories by year, birth weight, infection source, and timing of infection and patient and center characteristics associated with neonatal E coli infection and antibiotic susceptibility were assessed. RESULTS: A total of 721 infants (434 male [60.2%]; median age at E coli infection, 14 days [interquartile range, 1-33 days]) from 69 centers had at least 1 episode of E coli infection and available susceptibility results. No significant changes were observed over time in the overall annual proportions of antibiotic nonsusceptibility to ampicillin (mean [SD], 66.8% [1.5%]; range, 63.3% to 68.6%; estimated yearly change, −0.28% [95% CI, −1.75% to 1.18%]), nonsusceptibility to aminoglycosides (mean [SD], 16.8% [4.5%]; range, 10.7% to 23.2%; estimated yearly change, −0.85% [95% CI, −1.93% to 0.23%]), or extended-spectrum β-lactamase phenotype (mean [SD], 5.0% [3.7%]; range, 0% to 11.1%; estimated yearly change, 0.46% [95% CI, −0.18% to 1.11%]). No isolates with nonsusceptibility to carbapenems were identified. Among 218 infants with early-onset infection, 22 (10.1%) had isolates with nonsusceptibility to both ampicillin and gentamicin, the antibiotics most commonly administered to newborns as empirical therapy. CONCLUSIONS AND RELEVANCE: In this cohort study, nonsusceptibility to commonly administered antibiotics was found in substantial proportions of neonatal E coli isolates, with no significant change from 2009 to 2017. These findings may inform empirical antibiotic choices for newborn infants.